WAYS TO IMPROVE THE EDUCATIONAL SYSTEM OF THE REPUBLIC OF UZBEKISTAN BY APPLYING THE “FINNISH MIRACLE” (Scientific electronic journal "Labor Economics and Human Capital", 2023)
This paper outlines the results of introducing the education system called the “Finnish miracle” into the educational process of the country and indicates the results that the country was able to achieve using the implemented method. The main ways to further improve the educational system are also expressed.
Keywords: Higher education, highly qualified personnel, optimization of the educational process, practical application of the skills of the education received, training of highly qualified specialists.